Draft for History of Šabac District Court 1839–1865: Аccommodation and Judges - Stanković, Uroš; Drakić, Gordana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
The article shows the data on Šabac District Court’s accommodation and its judges from 1839, when judiciary in Serbia was reorganized according to provisions of so-called Turkish Constitution (1838), to 1865, i.e. introduction of the Organization of District Courts, which reshaped organization of first-degree judicature in Serbia. Opening paragraphs provide a brief account on the Šabac Magistrate founded during the First Serbian Uprising (1804–1813) and Šabac Nahyia/District Court, formed in 1823. Passages that follow up refer to accomodation of the court, placed in the Residence of Jevrem Obrenović, Prince Miloš Obrenović’s brother, and its detention facilities. The paper continues with fragments regarding judges of the Šabac District Court in the analyzed period. The authors’ foci of attention were criteria for election of judges, their personal qualities and acting in service.